Beyond Unidimensional Measurement of Corruption. (2nd January 2017) - Andersson, Staffan
Abstract : This article discusses the effects of standard corruption measurement, as used in comparative research, for its accuracy in estimating and understanding corruption. Implicitly, standard measurements treat corruption as a one-dimensional phenomenon (measured by a single score) that can vary in incidence between countries (or other geographical entities), but not in form. Such measurements also tend to equate corruption with bribery. This article argues that the degree to which one-dimensional bribery-focused measurements constitute a suitable proxy for corruption differs across countries (i.e., the measurement discrepancy is not random across countries). In particular, these measurements are ill-suited to capture corruption in established democracies with highly developed economies, where corruption is expected to center on gaining access to and influence within strong state institutions rather than on bribery. Sweden, a "least-corrupt" case, is used to illustrate the effects of relying on such measurements in such a setting, and to show that whereas bribery might be a relatively rare event, undue influence and interest conflicts can be a frequent occurrence.